Modelling exterior beam?column joints for seismic analysis of RC frame structures?. - Favvata, Maria J. (Earthquake engineering & structural dynamics.)
In common practice, the local response of beam?column joints is not considered for the seismic analysis of multistorey reinforced concrete (RC) frame structures, where these critical regions are typically assumed as rigid. Studies that incorporate the local effect of the joints in the seismic analysis of multistorey RC frame structures are limited. Identifying the main disadvantages of the analytical models that have been proposed so far, a behavioural model is developed for the simulation of the local inelastic response of exterior RC beam?column joints in multistorey RC frame structure. Special attention is given to the description of the main characteristics of the actual seismic response of the joints, including strength and stiffness degradation. The proposed model is incorporated as a rotational spring element in a general program for nonlinear static and dynamic analysis of structures, and a procedure for the evaluation of the required model parameters is also presented. The effectiveness of the proposed joint element model is demonstrated through comparisons with experimental data of 12 RC exterior joints reported in the literature. Moreover, using the proposed element, the influence of the local nonlinear response of RC exterior beam?column joints on the ductility requirements of columns and on the failure mode and overall seismic response of a multistorey RC frame structure is investigated. From the results of these analyses, it is concluded that the modelling of exterior RC joints with reduced capacity as rigid joints can lead to unconservative results and therefore to unsafe design.